Smart Riders 3D Sebagai Game Pengenalan Rambu Lalu Lintas Berbasis Android - Sulastianingsih, Febri; Kartono, R. (Jurnal Teknik Elektro, 2018)
Android smartphone, one of the entertainment media that is used by many people for games. Besides being an entertainment media, games can be used as educational media, such as the introduction of traffic signs. Knowledge of traffic signs on motorists influences the occurrence of traffic accidents. Therefore, the introduction of traffic signs is one of the efforts in controlling traffic. This is because knowledge of traffic signs is currently lacking. In this study, it will present the making of a Smart Rider application that aims to introduce traffic signs to prospective drivers and drivers of motorized vehicles. The software development method used is Waterfall, which includes communication, planning, modeling, construction and deployment. Application testing uses material testing, functionality, usability and portability. Usability testing is done by media experts and users. Users in this study were taken from Kebumen Vocational High School 1 students. From the results of testing the application as a whole, shows that the application has a good function. The test results can be seen from the material test reaching 94.4%, the user response reached 78.74%, and the results of testing by media experts reached 87.5%. Thus, the Smart Rider application is declared feasible to be used as a game for introducing Android-based traffic signs.